2003
DOI: 10.3801/iafss.fss.7-469
|View full text |Cite
|
Sign up to set email alerts
|

Application Of Water Sprays To Industrial Oil Cooker Fire

Abstract: Fourteen full-scale fire tests were conducted to determine the optimal design parameters of water-based protection systems against large industrial oil cooker fires. All but one test fires were self-ignited by heating the oil inside a test pan above its auto-ignition temperature. Three test mock-ups that simulated industrial oil cookers were fabricated for the tests: 3.0 m long by 2.4 m wide, 6.1 m long by 2.4 m wide, and 12.2 m long by 2.4 m wide. Three types of water spray systems utilizing 13 mm orifice spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Other changes in the oil properties included an increase in the specific heat or heat capacity, and a decrease in its viscosity. The specific heat of canola oil, C p , at room temperature is 1.91 kJ/kg.K, but its average value at the temperature range of 20 o C to 160 o C increases to 2.5 kJ/kg.K [24]. The bulk of the oil auto-ignited at 343 o C~362 o C in the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other changes in the oil properties included an increase in the specific heat or heat capacity, and a decrease in its viscosity. The specific heat of canola oil, C p , at room temperature is 1.91 kJ/kg.K, but its average value at the temperature range of 20 o C to 160 o C increases to 2.5 kJ/kg.K [24]. The bulk of the oil auto-ignited at 343 o C~362 o C in the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Nam [24] conducted a series of full-scale fire tests in which water spray was used to suppress large cooking oil fires associated with large industrial oil cookers. Test results showed that water spray was capable of extinguishing large oil fires and no vapour explosion was observed during suppression.…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6. Based on the known properties of other cooking oils and hydrocarbon fuels [2,12,13], the heat of combustion and the burning rate of canola oil are given as 39,200 kJ/kg and 0.0462 kg/m 2 s. The heat of gasification of canola oil is assumed to be 970 kJ/kg, the same value as ethyl alcohol in consideration of their similar burning rate (0.04 kg/ m 2 s) [13]. The fraction of heat of combustion of the oil that is transferred from the flame to the fuel is assumed to be 0.1 in consideration of fine water drops and their vapors in the flame.…”
Section: Fire Experimentsmentioning
confidence: 99%
“…The feasibility of using sprinkler water sprays for industrial oil cooker protection has been previously studied [2]. A series of full-scale fire tests were conducted in an outdoor facility involving three large industrial oil cooker mock-ups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation